The Combination of Project Construction Management and Lean Construction Techniques in the Architectural Project - Di Domenico, Francesco (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Main goal of Project Construction Management and Project Management is to delivery a project within scope, times and costs planned, obtaining a high quality standard. Instead, Lean Construction is focused on minimizing waste, in favor to creating maximum value for the client. The question to which this empirical research wants to answer is following: the integration of Project Construction Management and Lean Construction techniques could affect positively the respect of times and costs planned? To answer to the question it ideated a method that integrates the techniques of two methodologies. Then it applied in the architectural project of simulation in order to show the potentiality of the method. The workflow divided into three stages. At first stage, they identified the individual assegnments through Work Breakdown Structure. At second stage, it defined the Organizational Breakdown Structure. At last stage they planned the construction times and costs through Priced Bill of Quantity, Cost Breakdown Structure, Gantt Chart and Last Planner® System. The hypothesis on expected results deriving from the application of the method and they could led to thinking an improvement of project performance in terms of times and costs planned, respect to only Project Construction Management techniques. Future researches could be experimental, involving enterprises ed implementing the methodology in real study cases, using also the Building Information Modelling.